A comparative study and a simplified formula for punching shear design of concrete slabs with or without membrane tensile forces. (October 2021) - Deifalla, A.
Abstract: Punching shear failure of concrete slabs is brittle with very little warning, whether with or without membrane tensile forces. Tensile forces decrease the punching shear strength, which if not accounted for properly causes a premature failure. In addition, there is a lack of agreement between various design codes for the case of punching shear, whether with or without membrane tensile forces. The study aims to examine and refine the punching shear design of concrete slabs with or without membrane tensile forces. A state-of-the-art review of six decades of experimental testing of and models for RC elements subjected to punching shear with or without membrane tensile forces was conducted. In addition, the accuracy, consistency, and safety of the design provisions are assessed. Moreover, concluding remarks were outlined, which could be helpful in further development of existing design codes. Last but not least, an existing simplified punching shear strength formula for lightweight concrete slabs was adapted, further modified, proposed, and validated for normal-weight RC slabs with or without membrane tensile forces. The proposed formula is simple, yet accurate and makes physical sense as well as being compatible with the Critical Crack Theory.